Documentation, Coding, and Billing for Neurologic Services and Procedures - Busis, Neil A.; Montgomery, Robert; Cohen, Bruce H. (Seminars in Neurology, 2025)
Documentation, coding, and billing (claims submission) are foundational to neurologic practice in the United States, enabling accurate reimbursement, effective communication, and data-driven advancements in patient care, research, and education. Neurologists navigate complex regulatory frameworks and evolving payer guidelines, requiring meticulous attention to diagnostic coding, evaluation and management (E/M) services, and procedure-specific requirements. This chapter examines critical aspects of neurologic billing and coding, including ICD-10-CM (International Classification of Diseases, Tenth Revision, Clinical Modification) for diagnostic accuracy, updated E/M guidelines emphasizing medical decision-making and time, and new telemedicine codes. It highlights the best practices for procedure coding and the use of digital health technologies. The challenges posed by prior authorization are explored, alongside potential solutions like artificial intelligence-driven tools and policy reform. By prioritizing precision, compliance, and technological adaptation, neurologists can enhance patient outcomes, support practice sustainability, and contribute to the broader goals of equitable, efficient, and innovative neurologic care.
Keywords: CPT coding; ICD-10; neurology; prior authorization; telemedicine